1993
DOI: 10.1038/bjc.1993.409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on the aerobic and hypoxic cytotoxicity of SR4233 in HT-29 cells

Abstract: Summary We have observed that low pH can substantially potentiate the cytotoxic effect of the bioreductive drug SR4233 in aerobic human tumour cells. No such potentiation was observed under hypoxic conditions. This pH effect might be relevant both to the therapeutic effectiveness and to the normal tissue toxicity of this new agent.The bioreductive drug 1,2,4-Benzotriazin-3-amine 1,4-Dioxide (SR4233 or WIN59075) has been shown to have a remarkably selective toxicity for hypoxic cells (Zeman et al., 1986), a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…32 Finally, the intracellular pH is also found to be an independent factor, independent of the oxygenation status of the cells in determining the cytotoxicity of tirapazamine. 33 Even the hypoxic cancer cells with high pH showed diminished effects and non-hypoxic cells with low pH showed potentiated effects to tirapazamine. With regard to higher incidences of muscle cramps as ADRs, loss of mitochondrial membrane was hypothesized as the reason for muscle cramps.…”
Section: Discussionmentioning
confidence: 99%
“…32 Finally, the intracellular pH is also found to be an independent factor, independent of the oxygenation status of the cells in determining the cytotoxicity of tirapazamine. 33 Even the hypoxic cancer cells with high pH showed diminished effects and non-hypoxic cells with low pH showed potentiated effects to tirapazamine. With regard to higher incidences of muscle cramps as ADRs, loss of mitochondrial membrane was hypothesized as the reason for muscle cramps.…”
Section: Discussionmentioning
confidence: 99%
“…Expression level of CA IX in tumor cells were also found to alter sensitivity towards TPZ as demonstrated by Shin et al that CA IX-negative C33A cervical carcinoma cells were insensitive to TPZ, and ectopic expression of CA IX conferred TPZ sensitivity to these cells [48]. Moreover, TPZ has been shown to be more cytotoxic to cancer cells in acidic microenvironment [49,50]. Finally, cells that are defective in homologous recombination proteins or excision repair (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the prerequisite hypoxic environment, factors affecting TPZ sensitivity include: expression of reductive enzymes (which activates TPZ to toxic free radicals) [47], CA IX levels [48], acidic microenvironment [49,50], p53 status (cancer type-dependent) [43] as well as the presence of homologous recombination proteins for DNA repair [51]. The cytotoxic species of TPZ is believed to be a hydroxyl radical that is produced upon a one-electron reduction of TPZ by NADPH:cytochrome c (P450) reductase [52].…”
Section: Discussionmentioning
confidence: 99%
“…28 [Skarsgard 1993] Using a magnetic resonance imaging/PISTOL technique to directly measure oxygen levels in pre-clinical tumour models of NSCLC (H1975) and epidermoid carcinoma (A431) treated with TPZ, it was found that tumour growth was not directly related to oxygen levels, but other factors such as tumour permeation and TPZ bioreduction were probably involved as well as oxygen levels.…”
Section: [Hicks 2006]mentioning
confidence: 99%